Contribuição ao estudo da influência da utilização de agregados miúdos reciclados provenientes de usinas concreteiras na carbonatação do concreto - Iara Lilian Rocha de Abreu (2016)
This study aims to contribute to the investigation of the influence of the partial replacement of the natural fine aggregates by recycled fine aggregates obtained from the waste generated from the concrete truck mixer truck washing, evaluating its impact on the compressive strength, the workability, in the porosity and in the advance of the carbonation front of the concrete, since these factors directly interfere in the structural performance and the durability of the reinforced concrete structures. Carbonation is a problem that is worsening due to the increase in the concentration of carbon dioxide (CO2) in the atmosphere of large urban centers and the porosity of the concrete influences its capacity to absorb CO2. As the quality of the aggregate interferes in the porosity of the concrete, the investigation of the influence of the recycled aggregates becomes of extreme relevance to make feasible its use. In this study, two types of mixtures for development were used: in the first type, samples were made with 100% natural aggregate and, in the second, specimens with 30% natural aggregate replacement per recycled aggregate from the processing of the waste generated from the concrete truck washing of a concrete plant located in the metropolitan area of Belo Horizonte. Both were dosed in order to meet the specifications of ABNT NBR 6118: 2014 for structural specimens exposed to an environment with moderate aggression class, whose environmental classification is urban, which determines a relation to / c 0.60 and class of resistance to compression ratio 25 MPa. The test specimens were subjected to the accelerated carbonation test and exposed to controlled conditions of humidity, temperature and CO2 concentration. The results suggest that the partial replacement of the natural fines aggregates by recycled fines aggregates in the proportions used in this study slightly worsened the performance of the concrete in relation to the advance of the carbonation front. The compressive strength test attended the minimum requirements required by the Brazilian standard for the class of aggression studied. The oxygen permeability test presented, for the CPAR mixes, at 77 days, a value for the permeability coefficient 10.8% higher than that obtained for the CPP mixes. However, the mercury intrusion porosimetry test suggests that the void size found in the cementitious matrix composite is as important as the total pore volume when the results are analyzed.